The Impact of community empowerment programs: participant views on safety, well-being, and public agency collaboration - Ahmad, Noor Diyana Fazan; Zahari, Haliza Mohd; Wong, Mohd Muhaimin Ridwan; Shukor, Nurul Naqirah; Abas, Fuad; Husin, Wan Norhasniah Wan (International Journal of Studies in Social Sciences and Humanities, 2026)
Following the COVID-19 pandemic in 2020, the Malaysian government implemented various initiatives to enhance the quality of life for communities affected by the crisis. One such initiative involved offering grants to associations registered with the Malaysian Registrar of Societies (ROS). These grants were offered to empower local communities, improve their living standards, and ensure their safety and well-being. This study aims to assess the benefits of these funds to the community, specifically in safety, well-being, leadership, and collaboration with public agencies. A self-administered online survey was conducted among 750 respondents who participated in programs organized by the grant-receiving associations. The questionnaire comprised five sections: demographic information, community safety, well-being, leadership, and collaboration with public agencies. Findings from the survey were analysed using descriptive analysis in SPSS Version 22. Results indicate that respondents were strongly inclined to engage in safety activities, thereby contributing to enhanced community harmony. Furthermore, motivation to adopt a healthy lifestyle and to offer mutual support among community members increased, especially during emergencies. Participants also show greater confidence, have a clearer understanding of their roles within the community, and demonstrate a strong commitment to community development. Public agencies were perceived to be cooperative, attentive to the community's needs, and prepared for long-term collaboration. Findings suggest an improvement in the overall well-being of the community that was involved in the programs organised.